Titanium dioxide doped with nitrogen nanopowder prepared by hydrothermal method - Pusit Pookmanee (2018)
© 2018 Trans Tech Publications, Switzerland. Nitrogen-doped titanium dioxide (N-doped TiO2) nanopowder was successfully prepared by the hydrothermal method. Titanium isopropoxide and urea were used as the starting precursors. The hydrothermal reaction was controlled at 200 ºC for 2, 4 and 6 h. The white powder was obtained and dried for 24h. The crystal structure was identified by X-ray diffraction (XRD). A single phase of anatase structure was obtained without calcination steps. The morphology was investigated by field emission scanning electron microscopy (FESEM). The particles were irregular in shape and highly agglomerated. The chemical composition was determined by energy dispersive X-ray spectrometry (EDXS). The characteristic X-ray energy of titanium (Kα = 4.51 keV and Kβ = 4.93 keV), oxygen (Kα = 0.52 keV) and nitrogen (Kα = 0.39 keV) were observed. The functional group was identified by Fourier transform infrared spectrophotometry (FTIR). The wavenumbers in the range 668 to 1389 cm-1 corresponded to vibrations of Ti–O–Ti bond. The wavenumber in the range of 1442 to 1500 cm-1 could be attributed to the nitrogen species in the TiO2 network.